Agricultural development: New perspectives in a changing world - Otsuka, Keijiro; Fan, Shenggen (International Food Policy Research Institute, 2021)
Agricultural Development: New Perspectives in a Changing World is the first comprehensive exploration of key emerging issues facing developing-country agriculture today, from rapid urbanization to rural transformation to climate change. In this four-part volume, top experts offer the latest research in the field of agricultural development. Using new lenses to examine today’s biggest challenges, contributors address topics such as nutrition and health, gender and household decision-making, agrifood value chains, natural resource management, and political economy. The book also covers most developing regions, providing a critical global perspective at a time when many pressing challenges extend beyond national borders. Tying all this together, Agricultural Development explores policy options and strategies for developing sustainable agriculture and reducing food insecurity and malnutrition.